1995
DOI: 10.1139/g95-071
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal distribution of a repeated DNA sequence from C-genome heterochromatin and the identification of a new ribosomal DNA locus in the Avena genus

Abstract: Satellite DNA specific to the oat C genome was sequenced and located on chromosomes of diploid, tetraploid, and hexaploid Avena ssp. using in situ hybridization. The sequence was present on all seven C genome chromosome pairs and hybridized to the entire length of each chromosome, with the exception of the terminal segments of some chromosome pairs. Three chromosome pairs belonging to the A genome showed hybridization signals near the telomeres of their long arms. The existence of intergenomic chromosome rearr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
4
47
0
Order By: Relevance
“…The detection of imperfect subrepeats of 32 bp would indicate that the As120a family has evolved from duplications of shorter units. Moreover, the high number of nucleotide substitutions, deletions, and insertions found reflect the dynamic and rapid change of this tandemly repeated DNA sequence that is not as homogenized as other plant satellite sequences (16,27,28). A comparison with the Am1 satellite C-genome specific sequence, which showed a 92% homology among its monomers (16), confirms the independent evolution rates of each repetitive family.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The detection of imperfect subrepeats of 32 bp would indicate that the As120a family has evolved from duplications of shorter units. Moreover, the high number of nucleotide substitutions, deletions, and insertions found reflect the dynamic and rapid change of this tandemly repeated DNA sequence that is not as homogenized as other plant satellite sequences (16,27,28). A comparison with the Am1 satellite C-genome specific sequence, which showed a 92% homology among its monomers (16), confirms the independent evolution rates of each repetitive family.…”
Section: Discussionmentioning
confidence: 67%
“…Chromosome preparation, probe labeling and FISH were as described (16). Five DNA probes were used for FISH analysis: (i) Clone pTa71, containing a 9-kilobase EcoRI fragment including the 18S-5.8S-26S rDNA gene and spacer sequences from Triticum aestivum (18); (ii) clone pTa794, including a 410-bp 5S rDNA gene and intergeneric spacer isolated from T. aestivum (19); (iii and iv) clones pAs 120 and pAs 120a isolated from A. strigosa (this work); and (v) clone pAm1, a satellite DNA specific to the oat C genome containing an insert of 464 bp, isolated from A. murphyi (20).…”
Section: Plantmentioning
confidence: 99%
“…Chen and Armstrong, 1994;Jellen et al, 1994;Leggett and Markhand, 1995;Yang et al, 1999). Fominaya et al (1995) and Linares et al (1996) performed FISH analysis using a repeated DNA sequence (pAm1) specific to C-genome chromosomes. When total genomic DNA from A. eriantha was used in this study, one to three pairs of Cgenome chromosomes carrying A/D translocations were detected in four hexaploid and two tetraploid oats.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, whereas only three major rDNA loci were reported by in situ hybridization of radioactive probes (Jellen et a!., 1994), an additional minor locus was detected by fluorescence in situ hybridization (Fominaya et at., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Oat species are predominantly self-fertilizing, thus wild populations and landraces are usually made up of a mixture of several homozygous genotypes whereas cultivars are characterized by a single homozygous genotype (Singh et a!., 1973;Allard et at., 1993;Perez de la Vega et al, 1994). Therefore, although rDNA heterogeneity because of heterozygosity should be very low (Polanco & Perez de la Vega, 1995), heterogeneity caused by the presence of several loci should be common in polyploid oat species such as hexaploid oats in which three major NOR loci and a minor locus have been reported (Fominaya et a!., 1995). However, a survey of ribosomal DNA polymorphism showed that geographically diverse A. sativa cultivars displayed little rDNA variation whereas A. byzantina displayed more extensive polymorphism (Jellen et a!., 1994). Interest in the genetic variability and genetic relationships among Avena sativa L. landraces, breeding materials, ancestral and advanced cultivars and their implication in adaptedness and genetic improvement has increased recently, as demonstrated in several works ranging from quantitative character variability to isozyme and DNA polymorphisms (Souza & Sorrells, 1991a,b;Lynch & Frey, 1993;Moser & Lee, 1994 analysed from certain accessions.…”
mentioning
confidence: 99%